Molecular Profiling of Hyalinizing Clear Cell Carcinomas Revealed a Subset of Tumors Harboring a Novel EWSR1-CREM Fusion: Report of 3 Cases - Chapman, Erin; Skalova, Alena; Ptakova, Nikola; Martinek, Petr; Goytain, Angela; Tucker, Tracy; Xiong, Wei; Leader, Mary; Kudlow, Brian A; Haimes, Josh D; Hayes, Malcolm M; Bohus, Peter; et al. (The American journal of surgical pathology, 2018)
We describe a novel gene fusion, EWSR1-CREM, identified in 3 cases of clear cell carcinoma (CCC) using anchored multiplex polymerase chain reaction, a next-generation sequencing-based technique. CCC is a low-grade salivary tumor recently characterized to have EWSR1-ATF1 fusions in the majority of cases. Three cases of malignant tumor presenting in the base of tongue, lung, and nasopharynx were studied. All cases shared a clear cell morphology with hyalinized stroma, presence of mucin and p63 positivity and were initially diagnosed as mucoepidermoid carcinoma but were negative for evidence of any of the expected gene fusions. Anchored multiplex polymerase chain reaction demonstrated a EWSR1-CREM fusion in all 3 cases to confirm a diagnosis of CCC. This finding is biologically justified as CREM and ATF1 both belong to the CREB family of transcription factors. EWSR1-CREM fusions have not been previously reported in CCC and have only rarely been reported in other tumors. We show that the ability to discover novel gene variants with next-generation sequencing-based assays has clinical utility in the pathologic classification of fusion gene-associated tumors.
Keywords: Aged; Oncogene Fusion; vysoce účinné nukleotidové sekvenování; modulátor elementu responzivního pro cyklický AMP; Gene Expression Profiling; lidé; lidé středního věku; senioři; ženské pohlaví; nádory jazyka; Nasopharyngeal Neoplasms; Cyclic AMP Response Element Modulator; Female; mužské pohlaví; RNA-Binding Protein EWS; nádory plic; transkriptom; Tongue Neoplasms; stanovení celkové genové exprese; Middle Aged; protein EWS vázající RNA; adenokarcinom z jasných buněk; Humans; nádory nosohltanu; Male; High-Throughput Nucleotide Sequencing; onkogenní fúze; Lung Neoplasms; Transcriptome; Adenocarcinoma, Clear Cell